Accumulation of macronutrients in beetroot plant - Cardoso, Antonio I. I. [UNESP]; Magro, Felipe O.; Oliveira Júnior, Manoel X.; Abrahão, Camila [UNESP]; Tavares, Ana E. B. [UNESP]; Fernandes, Dirceu M. [UNESP] (Assoc Brasileira Horticultura, 2017)
Nutrient need in each development stage of plant is showed by nutrient accumulation curve; this is an important tool for fertilization recommendation. However, researches on vegetables with the objective to estimate these curves are scarce, mainly in the modern hybrids that show higher productivity potential and, probably, higher nutrient demand. In this study, the authors aimed to determine macronutrient accumulation of beetroot plants, hybrid Boro. The experiment was carried out in Sao Manuel, Sao Paulo State, Brazil. Five treatments [seasons of plant collection: 0, 14, 28, 43 and 60 days after transplanting (DAT)], considering that in each season 16 plants were collected (four replications of four plants each, in a randomized block design). We evaluated dry matter accumulation, and nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg) and sulphur (S) in plant shoot and root. The period of the highest demand for most of macronutrients was from 29 to 43 DAT. The decreasing order of macronutrients exported by the roots of the beetroot was K > N > P > Mg > S > Ca (376, 232, 45, 29, 21 and 13 mg/plant, respectively), and accumulated by the whole plant (shoot + root) was K > N > Mg > Ca > P > S (709, 404, 126, 113, 69 and 50 mg/plant, respectively).
Acúmulo de macronutrientes pela beterraba
Keywords: Beta vulgaris; Fertilization; Nutrients absorption; Nutritional demand